Death Certification: An Interactive Teaching Session - James H. Wykowski; Andrew M. Luks; Gabrielle Berger; Desiree A. Marshall (Association of American Medical Colleges, 2023)
Introduction Documentation of the cause of death is important for local and national epidemiology as well as for research and public health funding allocation. Despite this, many physicians lack the skills necessary to accurately complete a death certificate. Methods We created a 45-minute virtual workshop to improve skills in completing death certificates. Participants examined the role of death certificates in disease epidemiology and resource allocation for research and public health interventions, reviewed the components of a death certificate, and practiced correcting and filling out death certificates from actual patient cases. To assess the workshop, participants completed sample death certificates immediately before and after the workshop for two representative cases. Results Thirty-six internal medicine residents (17 PGY 1s, 12 PGY 2s, and seven PGY 3s) completed the workshop. Prior to the workshop, 89% of the sample death certificates contained one or more errors, compared with 46% postworkshop. Major errors, such as incorrect categorization of a cause of death, decreased from 58% preworkshop to 17% postworkshop. Learners expressed discomfort after realizing they had made errors in completing previous death certificates and noted a desire for continuing education and reference materials on this topic. Discussion Death certification is a key competency for physicians. Our virtual workshop improved participants' skills in completing death certificates. Although a significant number of errors remained after the workshop, most of these residual errors were minor and would not affect cause-of-death reporting. The durability of these improvements over time requires further study.